A novel gene family controls species-specific morphological traits in Hydra. - Konstantin Khalturin; Friederike Anton-Erxleben; Sylvia Sassmann; Jörg Wittlieb; Georg Hemmrich; Thomas C G Bosch (PLoS Biology, 2008)
Understanding the molecular events that underlie the evolution of morphological diversity is a major challenge in biology. Here, to identify genes whose expression correlates with species-specific morphologies, we compared transcriptomes of two closely related Hydra species. We find that species-specific differences in tentacle formation correlate with expression of a taxonomically restricted gene encoding a small secreted protein. We show that gain of function induces changes in morphology that mirror the phenotypic differences observed between species. These results suggest that "novel" genes may be involved in the generation of species-specific morphological traits.